2011
DOI: 10.1016/j.jbiomech.2011.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Regional analysis of dynamic deformation characteristics of native aortic valve leaflets

Abstract: Background The mechanical environment of the aortic valve (AV) has a significant impact on valve cellular biology and disease progression, but the regional variation in stretch across the AV leaflet is not well understood. This study, therefore, sought to quantify the regional variation in dynamic deformation characteristics of AV leaflets in the native mechanical environment in order to link leaflet stretch variation to reported AV calcification patterns. Methods Whole porcine AVs (n=6) were sutured into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…However, in general the results presented here are in good agreement with previous studies. For example, the radial stretches have been reported to be higher than the circumferential ones in porcine valves (Adamczyk et al, 2000; Weiler et al, 2011), with values of strains in the same range as our presented results. However, a direct comparison of strain values is not possible.…”
Section: Discussionsupporting
confidence: 87%
“…However, in general the results presented here are in good agreement with previous studies. For example, the radial stretches have been reported to be higher than the circumferential ones in porcine valves (Adamczyk et al, 2000; Weiler et al, 2011), with values of strains in the same range as our presented results. However, a direct comparison of strain values is not possible.…”
Section: Discussionsupporting
confidence: 87%
“…Computational modelling by the Yoganathan group recently showed regional strain variations in aortic valve tissue subjected to physiological stresses, with the highest stretch magnitude seen in the base and along the coaptation lines of the valve cusps, which is, interestingly, also where calcification is most often seen. 56 Additionally, in vitro studies by the Merryman group have demonstrated the strain dependence of apoptosis and nodule formation in valvular cells. 57 58 These studies suggest an important role of tissue stretch in the pathogenesis of valvular calcification, and highlight the complexities of studying cardiovascular cells exposed to a dynamic biomechanical environment.…”
Section: Effects Of Tissue Strainmentioning
confidence: 99%
“…It is possible that more than one of these components could be adversely affected in valve disease, with obvious consequences for the identification of an effective ameliorating strategy. Further compounding the challenge is the fact that the natural stretch environment in vivo is strongly anisotropic and heterogeneous 143 . We and other researchers have demonstrated that endothelial and interstitial cells respond differently to different patterns of cyclic stretch and shear stress, which exist in a localized geometry 101,144–147 .…”
Section: Molecular Mediators Of Valve Mechanobiologymentioning
confidence: 99%